Variability in power output during cycling in international Olympic-distance triathlon - Etxebarria, N.; D`Auria, S.; Anson, J. M.; Pyne, D. B.; Ferguson, R. A. (International Journal of Sports Physiology and Performance, 2014)
Purpose: The patterns of power output in the ~1-h cycle section of Olympic-distance triathlon races are not well documented. Here the authors establish a typical cycling-race profile derived from several International Triathlon Union elite-level draftinglegal triathlon races. Methods: The authors collated 12 different race power profiles from elite male triathletes (N = 5, age 25 ± 5 y, body mass 65.5 ± 5.6 kg; mean ± SD) during 7 international races. Power output was recorded using SRM cranks and analyzed with proprietary software. Results: The mean power output was 252 ± 33 W, or 3.9 ± 0.5 W/kg in relative terms, with a coefficient of variation of 71% ± 13%. Normalized power (power output an athlete could sustain if intensity were maintained constant without any variability) for the entire cycle section was 291 ± 29 W, or 40 ± 13 W higher than the actual mean power output. There were 34 ± 14 peaks of power output above 600 W and ~18% time spent at >100% of maximal aerobic power. Conclusion: Cycling during Olympic-distance triathlon, characterized by frequent and large power variations including repeat supramaximal efforts, equates to a higher workload than cycling at constant power.